Interfaith dialogue in India: Its need and challenges - Islam, Nasser Ul (Journal of Language, Literature, Social and Cultural Studies, 2023)
India has been the land of diverse cultures and religions over a long period of time. The adherents to different religions have been coexisting peacefully and sharing both the glories and the downfalls together. Though there is a long and well-established tradition of religious engagement and debate in India, the process of religious dialogue, particularly Hindu-Muslim dialogue, has yet to find a cohesive expression and a stable foundation on which to stand. Who isn’t aware about the riots, violence and killings on the name of religion in the history of India? The hatred and the disbelief against Muslims have dealt a huge blow for the unity and diversity of India. However, there is still hope for religious dialogue in India, as the country has been a pluralist culture for centuries and the people have lived through religious tolerance and coexistence. The only solution to this would be interfaith dialogue which is mandatory if not dynamic for everyone to have the understanding of different religions or belief systems. In this article, I would start with a brief introduction about interfaith dialogue, its history in India and then discuss in detail the need, importance and contemporary challenges of interfaith dialogue in India. This would help in understanding the dialogue between Hindus, Muslims, Christians, and Sikhs, as well as to eliminate prejudices and misunderstandings regarding each other's faiths. It would also assist in the achievement of common goals such as the establishment of justice and world peace, the protection of human rights, and the promotion of moral values.